1979
DOI: 10.1111/j.1432-1033.1979.tb12793.x
|View full text |Cite
|
Sign up to set email alerts
|

Sialic‐Acid Content of Low‐Density Lipoproteins Controls Their Binding and Uptake by Cultured Cells

Abstract: The (high-affinity receptor)-mediated uptake of homologous low-density (low-g) lipoproteins by cultured human arterial smooth muscle cells or human skin fibroblasts is controlled by the sialic acid content of low-g lipoprotein particles. This conclusion is derived from the following results .1. Gangliosides incubated with native low-@ lipoproteins associate with low-e lipoprotein particles.Low-Q lipoproteins modified by associated GL,,l, GGtetl, and GGtet2b + Gctet3 gangliosides are internalized by arterial sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…Recent studies [8] have pointed to the role of the net charge of LDL in its binding, internalisation and degradation by cultured skin fibroblasts. Removal of the sialic acid residues from LDL enhances its binding and uptake up to 100% relative to native LDL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies [8] have pointed to the role of the net charge of LDL in its binding, internalisation and degradation by cultured skin fibroblasts. Removal of the sialic acid residues from LDL enhances its binding and uptake up to 100% relative to native LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Normal human fibroblasts were grown from the skin explant of a normal infant as described previously [8] and were used for incubation experiments between the third and eight passages. Human skin fibroblasts deficient in LDL receptor (GM 1915) were obtained from the Institute for Medical Research (Camden, N.J., U.S.A.).…”
Section: Cell Liliesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] An early study by Filipovic [11] and co-authors showed that LDL modification enhanced cholesterol intake by cultured cells. Subsequently, naturally modified LDL types were found in human blood.…”
Section: Modified Ldl and Atherosclerosismentioning
confidence: 99%